PERILAKU AUDITOR MENYIKAPI MUNCULNYA KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE) DAN KESEHATAN KLIEN DALAM PROSES AUDIT DI KANTOR AKUNTAN PUBLIK (KAP) KOTA BENGKULU - Tia Fitri Sarioyonsi; Riswandi, Pedi; Yulianasari, Nina (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
This study aims to analyze the influence of auditor behavior, artificial intelligence, client health, and the audit process. The study was conducted at Public Accounting Firms (KAP) in Bengkulu City. The approach used in this research is quantitative, with data collection techniques through questionnaires. The obtained data were analyzed using multiple regression with the help of SPSS version 29.0. The results of the study show that auditor behavior (X1) has a significant influence on the audit process. In addition, artificial intelligence (X2) also has a significant influence on the audit process, while client health (X3) does not have a significant influence on the audit process (Y). Before the main analysis was conducted, the research instruments were tested through validity and reliability tests. The prerequisite tests included normality test, multicollinearity test, and heteroscedasticity test. The hypothesis testing in this study used multiple regression analysis. Overall, the results of this study indicate a significant influence of artificial intelligence on the audit process. Keywords: Auditor Behavior, Artificial Intelligence, Client Health, And Audit Process